2013
DOI: 10.4314/ajcem.v14i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic susceptibility of AmpC and ESBLs producing clinical isolates at a tertiary health care center in Kano, north-west Nigeria

Abstract: The increase in production of Extended Spectrum Beta Lactamase (ESBL) and Amp C beta lactamase among clinical isolates in our hospitals is of utmost importance. Failure to detect these enzymes in many of our hospitals has greatly led to treatment failure and uncontrolled spread of multi drug resistant pathogens. It was for this purpose that the present study was conducted to determine the prevalence, distribution and susceptibility pattern of Gram negative bacteria producing ESBLs and Amp C beta lactamases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
27
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 13 publications
11
27
6
Order By: Relevance
“…This agrees with the findings of Yusuf et al [27]. Similarly, there was no significant difference (p = 0.5006) in the prevalence of AmpC β-lactamase among isolates recovered from in-patients and out-patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This agrees with the findings of Yusuf et al [27]. Similarly, there was no significant difference (p = 0.5006) in the prevalence of AmpC β-lactamase among isolates recovered from in-patients and out-patients.…”
Section: Discussionsupporting
confidence: 82%
“…This is not in agreement with the findings of Yusuf et al [27] where isolates from urine were the predominant producers of AmpC β-lactamase. No reason could be adduced for this difference, albeit, the prevalence of AmpC β-lactamase differ significantly among Gram negative bacteria recovered from various clinical specimens (p = 0.0484).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding agrees with a study in India in which P. aeruginosa ranked the highest among bacterial isolates producing AmpC β-lactamase with 33.3%, but is however in contrast with a Nigerian study which showed E. coli as the highest producer of the enzyme. 20,21 Citrobacter species were the most prevalent producers of MBL (44.4%) and differs from previous studies. A study in Nigeria had shown E. coli (13.0%) and another study in Uganda showed a high prevalence of MBL genes (NDM-1, VIM and IMP) in K. pneumoniae compared with other GNB.…”
Section: Discussioncontrasting
confidence: 54%
“…In a previous study evaluating rectal swabs of pigs in Nigeria, Salmonella species ranked next to Klebsiella species in ESBL production (Ugwu et al, 2015). The finding is also in contrast to previous studies on human specimens in South, North-West and South-West Nigeria which observed Enterobacter species and Klebsiella species as the most prevalent producers of ESBL (Ogefere et al, 2015;Ogbolu et al, 2011;Yusuf et al, 2013). Salmonella species, which could be either diarrheagenic (non-typhoidal) or septicemic (typhoidal), can under stress, accept genetic materials from other bacteria, notably E. coli in the gastrointestinal tract (Aibinu et al, 2007).…”
Section: Detection Of Extended Spectrum Beta Lactamasecontrasting
confidence: 55%